Lewis superacidic catecholato phosphonium ions: phosphorus-ligand cooperative C-H Bond activation - Roth, Daniel; Stirn, Judith; Stephan, Douglas W.; Greb, Lutz (Journal of the American Chemical Society, 2021)
A series of catecholato phosphonium ions, including the first stable bis(catecholato)-substituted derivatives, are isolated and fully characterized. The cations rank among the most potent literature-known Lewis acids on the Gutmann-Beckett and ion affinity scales. In contrast to halogenated or multiply charged phosphorus cations, Lewis superacidity is imparted by structural constraints, as disclosed by energy decomposition analysis. The modular access provides a tunable scaffold while maintaining extreme affinity, demonstrated by the synthesis of a chiral Lewis superacid. The combination of electrophilic phosphorus and basic oxygen substituents leverages new reactivity modes by phosphorus-ligand cooperativity. With this, a phosphorus-mediated C-H bond activation is accomplished.